Hacienda Maranga como patrimonio agroindustrial de San Miguel - Avila Espichán, Soveyda (2023)
Agro-industrial heritage is a topic recently explored in Latin America, where new research is showing its importance in the heritage field. The objective of this research is to reveal how relevant the presence of agro-industrial heritage is, probably the only case study of this type in San Miguel district nowadays: Hacienda Maranga; its history, its actors through time, the objects and heritage values ​​that are attributed it. This peculiar hacienda was a milestone at different times in its history, the importance and influence even in the formation of the San Miguel district could be due to its presence.